1992
DOI: 10.1042/bj2810683
|View full text |Cite
|
Sign up to set email alerts
|

Different pathways of inositol phosphate metabolism in intact neonatal rat hearts and isolated cardiomyocytes

Abstract: In most tissues stimulation of the phosphatidylinositol turnover pathway causes release of inositol 1,4,5-trisphosphate [Ins(1,4,5)P3], which is subsequently metabolized to a wide range of inositol phosphate isomers deriving from both phosphorylation and dephosphorylation reactions. However, addition of noradrenaline to isolated intact neonatal-rat hearts generated only those inositol phosphates produced by dephosphorylation of Ins(1,4,5)P3. Products of the InsP3 kinase pathway were absent from the profiles, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Also, inositol phosphates may be formed from other sources than IP3, in particular in intact cardiac tissue . It is worth noting that Guse et al (1991) found a 6-8-fold increase in the level of radiolabelled IP3 after al-adrenoceptor stimulation, which is well above the 2-3-fold increase most investigators have observed when using incorporation of radiolabelled inositol (Steinberg et al 1989;Ventura et al 1991;Woodcock et al 1992Woodcock et al & 1993. Furthermore, the transient nature of the inhibitory effect reported by Guse et al (1991) is not easily reconciled with the mechanisms currently believed to be involved in the modulation of the phosphoinositide system by CAMP-elevating compounds in various cell types, e.g.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Also, inositol phosphates may be formed from other sources than IP3, in particular in intact cardiac tissue . It is worth noting that Guse et al (1991) found a 6-8-fold increase in the level of radiolabelled IP3 after al-adrenoceptor stimulation, which is well above the 2-3-fold increase most investigators have observed when using incorporation of radiolabelled inositol (Steinberg et al 1989;Ventura et al 1991;Woodcock et al 1992Woodcock et al & 1993. Furthermore, the transient nature of the inhibitory effect reported by Guse et al (1991) is not easily reconciled with the mechanisms currently believed to be involved in the modulation of the phosphoinositide system by CAMP-elevating compounds in various cell types, e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Also, both the time course and the magnitude of the IP, accumulation in response to purinergic stimulation of adult rat cardiomyocytes (Puceat & Vassort 1996) were very similar to the response observed after a,-adrenoceptor stimulation in the present study. In most studies that examined the accumulation of radiolabelled ( i,4,5)IP3, an initial, 2-3-fold increase was observed (Steinberg et al 1989;Ventura et al 1991;Woodcock et al 1992Woodcock et al & 1993, although Guse et al (1989) found an increase that was at least 8-fold. The increased IP, levels either declined to control values within 1-2 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…␣ 1 -AR are not detected on mast cells or cardiac fibroblasts and thus contribution to norepinephrine-dependent responses from these cell types can be discounted. Furthermore, PLC responses in cardiomyocytes differ in terms of rate and in inositol phosphate isomers generated from responses in other cell types (51).…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation of the data is that receptor stimulation leads primarily to the release of Ins(l,4)P2 which is broken down to Ins(4)Pl and a little Ins(1)PI. Only a small amount of Ins(1,4,5)P3 is released and this accounts for the absence of phosphorylation products of the compound (Woodcock et al 1987).…”
Section: Effects Of Neomycin On the Inositol Phosphate Reponse To Normentioning
confidence: 99%